Efeitos de retardantes de fogo sobre o crescimento inicial de espécies florestais - Ximenes, Elen Silma Oliveira Cruz (2020)
- Natural or man-made forest fires are one of the most devastating disturbances. Flame retardant products improve water efficiency in fire fighting. Nevertheless, its effects on the environment are little clarified. Research into the effects of these products on the seed bank and plant growth can help in defining effective and safe ones. Therefore, the aim of this work was to evaluate the effects of fire retardants on the initial growth of forest species. In this study, the first chapter contains the theoretical foundation whose purpose is to base the other chapters. In the second chapter analyzed, the initial growth of Schizolobium amazonicum under the fire retardant Phos-Chek WD881®, Hold Fire® and Nutrigel® hydrochloride polymer used via substrate and via leaf. Destructive growth analyses of the seedlings were performed. The results show that: Phos-Chek WD881 applied via substrate or non- harmful leaf or initial growth of S. amazonicum; successive 15 mL L-1 applications of Hold Fire via decreased leaf or dry mass of seedlings, while substrate applications do not interfere with species growth; S. amazonicum seedlings recover over time from stresses caused by hydrogel overhydration via substrate, applications of Nutrigel 0.50 g L-1 via leaf potential for potentiation or growth of S. amazonicum seedlings. In the third chapter, tested for emergence and growth of Handroanthus ochraceus and Tabebuia roseoalba under the Phos-Chek WD881, Hold Fire and Nutrigel tests used via substrate. Seed emergence was evaluated by emergence speed index, percentage and mean emergence time. The effects are imposed through destructive growth analyses. To perform the photosynthetic performance tested, if there is chlorophyll fluorescence from 60 DAS. The emergence of the seedlings of Handroanthus ochraceus and Tabebuia roseoalba does not change with the tests of the tested products. Phos-Chek WD881 applications up to 5 mL L-1 have positive effects on the growth of Handroanthus ochraceus and Tabebuia roseoalba. Increasing applications of Hold Fire to a concentration of 8.00 mL L1 favor the growth of Tabebuia roseoalba. Hand changes respond to Hold Fire changes, after successive applications, diameter growth shows a positive trend from 9.6 mL L1 of the retardant. The 0.50 g L-1 to 0.88 g L-1 range of the Nutrigel hydrochloride polymer stimulates the diameter growth of Handroanthus ochraceus and Tabebuia roseoalba. The fluorescence parameters used as fire retardants and hydrochloride polymer do not affect photosynthetic processes related to photosystem II of the species Handroanthus ochraceus and Tabebuia roseoalba.